International tourists’ demand on food tourism in Kuala Lumpur - Noordin, Noor Syazana (2017)
The purpose of this paper is to identify the demand on food tourism in Kuala Lumpur among the International Tourists’ who have visited Kuala Lumpur. Food tourism nowadays plays an important role in branding a destination of the place. Kuala Lumpur is well known for varieties of cuisine and this can make it as a food tourism destination in order to attract the International Tourists’ to revisit the place. This study is using quantitative approach to measure the food preference, demand and perceived image of Kuala Lumpur on food tourism in Kuala Lumpur. Variable that were identified to measure in this study are the food preference patterns, demand on food tourism and how international tourists’ perceived image of Kuala Lumpur on food tourism. In addition, survey questionnaire is chosen because it is consider the most productive tool to collect information that represents the general views of the group. A total of 146 respondents was sampled. Analysis that were used are descriptive and frequency analysis. The findings indicated that the International Tourists’ agree to suggest Kuala Lumpur as a food tourism destination. They are interested with the cuisine such as Arabic Cuisine, Thai Cuisine, Malay Cuisine and Indian Cuisine. Overall, they love to explore different type of cuisine in Kuala Lumpur and more studies can be improve on food tourism in Kuala Lumpur for future researchers.